Design and Analysis of High Flexion Femoral Component for Total Knee Arthroplasty (TKA) - Hanafi Seman, Mohammad; Shuib, Solehuddin; Afzan bin Mohd Anuar, Mohd; Ahmed Shokri, Amran (International Journal of Engineering and Technology, 2018)
In the early development of TKA, disability of traditional prosthetic knee to consistently reach 115-degree angle raised concerns about functional limitations for demanding high flexion patients. The need for high flexion at 120 degrees in certain patients especially in some ethnic population that requires high flexion for various social and religious activities has been proven by clinical experience. This study was carried out through a static structural analysis of implanted knee underwent deep flexion motion using ANSYS R18. Flexion angles of 0, 90, 135 and 165 degrees with different net force based on a percentage of body weight were applied on the prosthetic knee model. The von Mises stress, shear stress, contact pressure and total deformation at tibial insert were observed and compared to find the optimal design for further optimization. The optimization includes increasing the maximum thickness of polyethylene tibial insert, increasing the conformity between femoral and tibial insert, also changing the post-cam contact features by using flat on flat, flat on a curve, and curve on a curve. Increasing the average conformity of tibiofemoral interface has successfully reduced the von Mises stress, shear stress and contact pressure about 24.4%, 23%, and 40.9%, respectively.Â Â Â